Molecular mechanisms underlying hematophagia revealed by comparative analyses of leech genomes. (11th April 2023) - Zheng, Jinghui; Wang, Xiaobo; Feng, Tong; Rehman, Saif ur; Yan, Xiuying; Shan, Huiquan; Ma, Xiaocong; Zhou, Weiguan; Xu, Wenhua; Lu, Liying; Liu, Jiasheng; Luo, Xier; et al.
Abstract: Background: Leeches have been used in traditional Chinese medicine since prehistoric times to treat a spectrum of ailments, but very little is known about their physiological, genetic, and evolutionary characteristics. Findings: We sequenced and assembled chromosome-level genomes of 3 leech species (bloodsucking Hirudo nipponia and Hirudinaria manillensis and nonbloodsucking Whitmania pigra ). The dynamic population histories and genome-wide expression patterns of the 2 bloodsucking leech species were found to be similar. A combined analysis of the genomic and transcriptional data revealed that the bloodsucking leeches have a presumably enhanced auditory sense for prey location in relatively deep fresh water. The copy number of genes related to anticoagulation, analgesia, and anti-inflammation increased in the bloodsucking leeches, and their gene expressions responded dynamically to the bloodsucking process. Furthermore, the expanded FBN1 gene family may help in rapid body swelling of leeches after bloodsucking, and the expanded GLB3 gene family may be associated with long-term storage of prey blood in a leech's body. Conclusions: The high-quality reference genomes and comprehensive datasets obtained in this study may facilitate innovations in the artificial culture and strain optimization of leeches.